Getting By or Getting Ahead on Social Networking Sites? The Role of Social Capital in Happiness and Well-Being. Issue 2 (3rd April 2018) - Munzel, Andreas; Galan, Jean-Philippe; Meyer-Waarden, Lars
ABSTRACT: By March 2017, Facebook had more than 1.94 billion active users monthly. Even as firms increasingly invest in social media, however, businesses appear only moderately satisfied with the bottom line of such social commerce efforts. To assist future efforts in social commerce, this research builds on social capital theory to investigate the effects of individual social interactions on social networking sites (SNSs) on users' happiness and well-being by examining how size and intimacy of the social network online and the mediating influence of two social capital facets, bonding and bridging, impact those outcomes. Among 2, 116 Facebook users, intimacy and network size affect well-being, through social capital. The findings reveal the importance of getting ahead (i.e., bridging social capital) rather than getting by (i.e., bonding social capital) among SNS users who seek novel information and experiences. The results imply that social interactions through SNSs are valuable for individuals and firms, because they guide efforts in improving social capital—and bridging social capital in particular—to improve the individual's well-being.